Establishing the ’Historical Dictionary of Switzerland’: an authoritative new source for the historiography of science in Switzerland - Neuenschwander, Erwin (Circumscribere International Journal for the History of Science, 2018)
The Historical Dictionary of Switzerland (HDS) covers the history of humankind in the geographical area of today’s Switzerland from the very beginning in Paleolithic times up to the twenty-first century. The HDS comprises articles in four broad categories: biographies (35%), articles on families and genealogy (10%), geographical entries (30%) and articles on thematic contributions (25%). The HDS was published in parallel in each of the three major Swiss national languages German, French, and Italian from 2002 to 2014. Each edition comprises 13 volumes of about 10,000 pages. In 1997, the HDS Board of Trustees decided to commemorate the 150th anniversary of the founding of the Swiss Confederation in 1848 with an internet publication of the HDS, which was simultaneously being published and which will now be augmented by multimedia and linked data (cf. www.hls-dhs-dss.ch). Our contribution describes the complex editorial processes of the whole subject area of mathematics and natural sciences in the HDS—covering about 1,200 biographies and approximately 40 thematic articles—supervised by the author and his working group in the years 1994−2014. As a trained mathematician and historian of science, and as scientific advisor for the HDS’s entire subject area of mathematics and the natural sciences, I wrote this article with the aim of sharing my experiences in representing the history of science in a general historical encyclopedia. The processes described below may perhaps be useful to other natural scientists or proper historians who intend to undertake similar projects.